2022
DOI: 10.3389/fcomm.2022.903015
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Prominence Marking in Semi-Spontaneous YouTube Monologs: The Interaction of Intonation and Eyebrow Movements

Abstract: Both facial expressions like eyebrow movements and prosodic characteristics like pitch height and the position of the pitch accent relative to the prominent syllable play an important role in prominence marking, which in turn is used by YouTubers and other public speakers alike to engage their audience. We analyze the co-occurrence of eyebrow movements and pitch accents of differing prominence levels produced by a sample of English-speaking YouTubers, and the height and position of those pitch accents. We anno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Unlike the other studies mentioned above, Berger and Zellers [68] used naturalistic data-semi-spontaneous YouTube monologs-to investigate the interaction of intonation and eyebrow movement. On the basis of automatic OpenFace annotations and manual pitch annotations, the authors found evidence of correlations between "pitch height and eyebrow movements .…”
Section: Facial Gestures and Audiovisual Prosodymentioning
confidence: 99%
See 3 more Smart Citations
“…Unlike the other studies mentioned above, Berger and Zellers [68] used naturalistic data-semi-spontaneous YouTube monologs-to investigate the interaction of intonation and eyebrow movement. On the basis of automatic OpenFace annotations and manual pitch annotations, the authors found evidence of correlations between "pitch height and eyebrow movements .…”
Section: Facial Gestures and Audiovisual Prosodymentioning
confidence: 99%
“…. for at least some of the measures for all speakers" [68] (p. 1). Moreover, they went beyond previous studies aiming to "investigate the relationships between data in the form of contours rather than individual points" [68] (p. 10).…”
Section: Facial Gestures and Audiovisual Prosodymentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, no relation was found between eyebrow movement and OVER AND OVER. Measuring pitch movement may shed light on this result, given the interaction between eyebrow movement and intonational contours (e.g Berger & Zellers 2022)…”
mentioning
confidence: 99%